Odpowiedź :
Odpowiedź:
zad.27.
a) 2*(-3)+6= -6+6= 0
-5*(-8) -16= 40-16= 24
2*(-5) +3 *(-2)= -10 + (-6)= - 16
8-6*(-5) = 8+30=38
b) 6- (-16) : (-8)= 6-2= 4
5*(-2) - (-2)*6= -10 -(-12)= -10+12= 2
( 2-6)*(-8)= 32
-5*(-6-10)= -5 *(-16)= 80
c) -3 *(-1) -(-10)*4= 3 - (-40)= 3+40= 43
(-5-6) :(-11_= -11 : (-11)= 1
24 : (-3-5)= 24 : (-8)= - 3
(-8+10) : (-7-4)= 2: (-11)= - 2/11
zad.28
a)
6+12
----------- * (-2)= 3* (-2)= -6
6
-8+20
-------------- *(-3)= 6*(-3)= - 18
2
b) -10+16
------------ : (-1)= -2 : (-1)= 2
-3
-7 - 5
----------- :3= 6:3= 2
-2
c) -12 +10 -6+3
-------------- + ------------- = -1 + (-1)= - 2
2 3
- 12 -6 +(-8)-(-4) -26 +4 - 22
---------------------- = --------------- = ------------- = 4 i 2/5
-3-2 -5 -5
Szczegółowe wyjaśnienie: